1978
DOI: 10.1029/rs013i004p00717
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated measurements of ELF transmission anomalies and the precipitation of energetic particles into the ionosphere

Abstract: Stimulated by previous findings of a positive qualitative correlation between anomalous ELF signal levels and the occurrence of significant fluxes of precipitating energetic particles, coordinated exercises were conducted between satellite measurements of the precipitating particles and ELF transmissions between the US Navy Wisconsin Test Facility and receiving stations in Maryland, Greenland, Norway, and Italy. Significant fluxes of precipitating electrons were often measured with the Lockheed pay load on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The presence of finite conductivity, which increases with height, makes the lower and middle atmosphere to act as dissipative waveguide. In this height region, energetic electrons are precipitated and complicate the transmitting properties of the medium (Imhof et al, 1978). Electromagnetic waves in the ELF/VLF range generated from a source on or near the Earth's surface such as lightning/man made transmitters, propagate over long distances through the wave-guide by the process of internal reflection (Budden, 1985;Barr et al, 2000).…”
Section: Wave Energy Transfer In the Earth-ionosphere Waveguidementioning
confidence: 99%
“…The presence of finite conductivity, which increases with height, makes the lower and middle atmosphere to act as dissipative waveguide. In this height region, energetic electrons are precipitated and complicate the transmitting properties of the medium (Imhof et al, 1978). Electromagnetic waves in the ELF/VLF range generated from a source on or near the Earth's surface such as lightning/man made transmitters, propagate over long distances through the wave-guide by the process of internal reflection (Budden, 1985;Barr et al, 2000).…”
Section: Wave Energy Transfer In the Earth-ionosphere Waveguidementioning
confidence: 99%
“…It is readily apparent from exceptions to this trend occurred during October [16][17][18] and day of month). It is readily apparent from Fig.…”
Section: Correlation With Geomagnetic Activitymentioning
confidence: 93%
“…Because some previous ELF field-strength variations appeared to be correlated with geomagnetic activity [14] - [16], it would be of interest to compare the 1976-1978 measurements with geomagnetic activity. Presented in Figs.…”
Section: Correlation With Geomagnetic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Because energetic particle precipitation into the D region tends to increase ionization, making the ionosphere more "daylike" by lowering the effective reflecting height and improving excitation, the observed nighttime field strength decreases are in the opposite sense to what would have been expected. Recently, from coordinated satellite and ELF field strength measurements, Imhof et al [1978] have found that direct particle precipitation into the atmosphere can cause ELF transmission anomalies. In these anomalies the signal strengths may be either attenuated or enhanced depending upon the spatial extent and location of the ionization.…”
Section: October Measurementsmentioning
confidence: 99%